Principal Leadership Practices in Enhancing the Quality of Primary Education: A Case Study from Bandar Dua District - Cut Zahara; Saiful Bahri; Iskandar Iskandar (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2026)
This study examines how school principals implement leadership strategies that improve the quality of primary education through the organised application of essential managerial functions—planning, organizing, implementing, and evaluating (POAE). The research employed a qualitative multi-site case study design commenced in two public primary schools in the Bandar Dua District, each representing distinct accreditation levels. Data were produced via comprehensive interviews, participant observation, and document analysis, and were thematically evaluated through triangulation to guarantee analytical rigor and reliability. The findings indicate that effective principals perceive leadership as a process rather than a collection of discrete actions. Principals convert collective school visions into data-driven planning, coordinate resources through collaborative and decentralized frameworks, enhance instructional quality through systematic oversight and ongoing professional development, and integrate evaluative practices grounded in learning outcomes and performance metrics to facilitate continuous improvement. These techniques exemplify a cohesive implementation of dispersed, transformational, instructional, and learning-centred leadership, tailored to specific contextual situations. Nonetheless, the efficacy of leadership is limited by inconsistent teacher capabilities, administrative requirements, and variations in resources among schools. This study enhances the educational leadership literature by promoting a process-oriented comprehension of principal leadership that connects leadership theory with routine managerial practice. The findings highlight the necessity of cohesive integration of POAE functions, participatory governance, and evidence-based decision-making to maintain quality enhancement in primary schools, affecting principal preparation and school-based management policy.